(untitled) (The Pakistan Development Review, 2013)
The term deindustrialisation refers to the process of socio-economic changes taking place due to reduction in the industrial capacity and/or the loss of industrial potential of an economy. This also connotes the secular decline in the share of industrial sector employment as observed in developed countries since 1970s. The secular shift from manufacturing to services sector reflects the impact of discrepancy in productivity growth between the said sectors. A faster rise in productivity in manufacturing sector than in services switches the employment from manufacturing to the services sector, as suggested by Rowthorn and Ramaswamy (1997). Generally, deindustrialisation is considered as the natural outcome of economic development because it involves the transformation from primitive agriculture-based economy to the modern industrial-based. After the establishment of manufacturing sector, the long-run economic growth stimulates an innovation-based economy implying the services sector’s growth [Galor (2005)]. However, the process requires a gradual shift accompanied by allied institutional and infrastructural reforms and the process of deindustrialisation occurs at the later stage of development.